(untitled) (Economics and region, 2025)
The basis of economic development is the theory of economic development. During the development of this work, the theory of economic development was first defined, its specific features were investigated for Azerbaijan, and the theory of economic development was adopted as the basis for the economic development of the country. Actuality of economic development means dynamic and stable development of economy in a country. This includes the growth of jobs, the use of new technologies and the achievement of solutions to social issues. Economic development is important for the country`s recovery, job creation and rapid development of citizens. It is explained as the growth of production, consumption and trade in the economic system of that country or region. This broad category covers various areas such as the growth of national income, expansion of industry, development in technology, changes in the labor market and rising living standards. During the years of independence, the Republic of Azerbaijan has already made the transition to market economic relations. Thus, macroeconomic stability has been achieved, successful strategies have been developed and implemented, consistent measures are being implemented at the microeconomic level, and entrepreneurial activity is full supported. From this point of view, determining the directions of the economic development of the Republic of Azerbaijan in modern conditions is one of the main problems. The problem of creating conditions for economic development remains very relevant in modern times. Globalization, technological revolution, economic crises and geopolitical changes require new approaches to ensure sustainable and sustainable development of countries. In this regard, the formation of conditions for economic development can be possible with the joint efforts of the public and private sectors. Economic development is an important factor for ensuring sustainable prosperity and social stability of any state. However, it is very important to carry out this process not artificially, but through sustainable and stable economic policies. In this regard, creating optimal conditions for economic development faces many obstacles. The initiative to create optimal conditions for economic development requires a comprehensive approach. Infrastructure, education, political stability, financial resources and international economic relations should be provided with sustainable and long-term economic strategies, not artificial ones. A systematic solution to these problems can accelerate economic development.